Cognitive behavioural therapy and short-term psychoanalytical psychotherapy versus a brief psychosocial intervention in adolescents with unipolar major depressive disorder (IMPACT): a multicentre, pragmatic, observer-blind, randomised controlled superiority trial. (February 2017) - Goodyer, Ian M; Reynolds, Shirley; Barrett, Barbara; Byford, Sarah; Dubicka, Bernadka; Hill, Jonathan; Holland, Fiona; Kelvin, Raphael; Midgley, Nick; Roberts, Chris; Senior, Rob; Target, Mary; et al.
Summary: Background: Psychological treatments for adolescents with unipolar major depressive disorder are associated with diagnostic remission within 28 weeks in 65–70% of patients. We aimed to assess the medium-term effects and costs of psychological therapies on maintenance of reduced depression symptoms 12 months after treatment. Methods: We did this multicentre, pragmatic, observer-blind, randomised controlled superiority trial (IMPACT) at 15 National Health Service child and adolescent mental health service (CAMHS) clinics in three regions in England. Adolescent patients (aged 11–17 years) with a diagnosis of DSM IV major depressive disorder were randomly assigned (1:1:1), via a web-based randomisation service, to receive cognitive behavioural therapy (CBT) or short-term psychoanalytical therapy versus a reference brief psychological intervention. Randomisation was stochastically minimised by age, sex, self-reported depression sum score, and region. Patients and clinicians were aware of group allocation, but allocation was concealed from outcome assessors. Patients were followed up and reassessed at weeks 6, 12, 36, 52, and 86 post-randomisation. The primary outcome was self-reported depression symptoms at weeks 36, 52, and 86, as measured with the self-reported Mood and Feelings Questionnaire (MFQ). Because our aim was to compare the two psychological therapies with the brief psychosocial intervention, we first established whether CBT was inferior to short-term psychoanalytical psychotherapy for the same outcome. Primary analysis was by intention to treat. This trial is registered with Current Controlled Trials, number ISRCTN83033550. Findings: Between June 29, 2010, and Jan 17, 2013, we randomly assigned 470 patients to receive the brief psychosocial intervention (n=158), CBT (n=155), or short-term psychoanalytical therapy (n=157); 465 patients comprised the intention-to-treat population. 392 (84%) patients had available data for primary analysis by the end of follow-up. Treatment fidelity and differentiation were established between the three interventions. The median number of treatment sessions differed significantly between patients in the brief psychosocial intervention group (n=6 [IQR 4–11]), CBT group (n=9 [5–14]), and short-term psychoanalytical therapy group (n=11 [5–23]; p<0·0001), but there was no difference between groups in the average duration of treatment (27·5 [SD 21·5], 24·9 [17·7], 27·9 [16·8] weeks, respectively; Kruskal–Wallis p=0·238). Self-reported depression symptoms did not differ significantly between patients given CBT and those given short-term psychoanalytical therapy at weeks 36 (treatment effect 0·179, 95% CI −3·731 to 4·088; p=0·929), 52 (0·307, −3·161 to 3·774; p=0·862), or 86 (0·578, −2·948 to 4·104; p=0·748). These two psychological treatments had no superiority effect compared with brief psychosocial intervention at weeks 36 (treatment effect −3·234, 95% CI −6·611 to 0·143; p=0·061), 52 (−2·806, −5·790 to 0·177; p=0·065), or 86 (−1·898, −4·922 to 1·126; p=0·219). Physical adverse events (self-reported breathing problems, sleep disturbances, drowsiness or tiredness, nausea, sweating, and being restless or overactive) did not differ between the groups. Total costs of the trial interventions did not differ significantly between treatment groups. Interpretation: We found no evidence for the superiority of CBT or short-term psychoanalytical therapy compared with a brief psychosocial intervention in maintenance of reduced depression symptoms 12 months after treatment. Short-term psychoanalytical therapy was as effective as CBT and, together with brief psychosocial intervention, offers additional patient choice for psychological therapy, alongside CBT, for adolescents with moderate to severe depression who are attending routine specialist CAMHS clinics. Funding: National Institute for Health Research (NIHR) Health Technology Assessment (HTA) programme, and the Department of Health.